Clinical characteristics and treatment efficacy in patients with primary severe IGF-1 deficiency treated with recombinant IGF-1 - Denaite, Dovile; Navardauskaite, Ruta (Frontiers in Pediatrics, 2024)
To evaluate the clinical characteristics and treatment efficacy of patients with severe primary IGF-1 deficiency (PSIGFD) using a recombinant IGF-1 (rhIGF-1).To examine the clinical characteristics of patients with PSIGFD before starting treatment with a rIGF-1. To assess the height changes in patients with PSIGFD, before and after treatment with a rhIGF-1. To analyze the clinical characteristics, side effect frequency, and treatment efficacy with a rhIGF-1 analog in patients with PSIGFD.Denaite D. et al.A retrospective analysis was conducted on patients with PSIGFD treated with the rhIGF-1 (mecasermin). Data were collected from patients' medical records, focusing on the impact of treatment on their growth and monitoring any side effects.The study showed that treatment with rhIGF-1 positively affects growth rate, especially in the first years of treatment. However, the growth rate decreases over time. The change in height from the beginning to the end of the treatment was 0.76±0.64 SD, with the first quartile at 0.29 SD and the third quartile at 1.14 SD. During the treatment period, patients' average body mass increased by 0.37±1.35 SD, with the first quartile at -0.33 SD and the third quartile at 0.92 SD. Side effects occurred in 50 % of patients, with 40 % of patients treated with rhIGF-1 experiencing hypoglycemia during treatment.Conclusions: Treatment with rhIGF-1 is effective in treating patients with PSIGFD, causing significant improvement in growth, but requires continuous monitoring and treatment adjustment.Recommendations: Further research is necessary with larger patient cohorts to determine optimal treatment doses and intervals, as well as to evaluate the long-term effects of the treatment on patients' health.